2018
DOI: 10.1038/s41598-018-30581-9
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific associations of infants’ gut microbiome with arsenic exposure in a US population

Abstract: Arsenic is a ubiquitous environmental toxicant with antimicrobial properties that can be found in food and drinking water. The influence of arsenic exposure on the composition of the human microbiome in US populations remains unknown, particularly during the vulnerable infant period. We investigated the relationship between arsenic exposure and gut microbiome composition in 204 infants prospectively followed as part of the New Hampshire Birth Cohort Study. Infant urine was analyzed for total arsenic concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 89 publications
0
36
0
2
Order By: Relevance
“…If the child was no longer using diapers, parents were provided an acid-washed receptacle that fit into the toilet to collect a urine-free stool sample (Supplementary Methods). Established protocols were followed for 16S rRNA gene sequencing and data processing (Supplementary Methods) [67][68][69][70][71][72] . A subset of DNA samples (from 6-week and 1-year stools) also underwent metagenomic sequencing at Marine Biological Laboratory as previously described (Supplementary Methods) [73][74][75] .…”
Section: Methodsmentioning
confidence: 99%
“…If the child was no longer using diapers, parents were provided an acid-washed receptacle that fit into the toilet to collect a urine-free stool sample (Supplementary Methods). Established protocols were followed for 16S rRNA gene sequencing and data processing (Supplementary Methods) [67][68][69][70][71][72] . A subset of DNA samples (from 6-week and 1-year stools) also underwent metagenomic sequencing at Marine Biological Laboratory as previously described (Supplementary Methods) [73][74][75] .…”
Section: Methodsmentioning
confidence: 99%
“…In a cohort of US infants with low to moderate arsenic exposure, microbes representing 8 genera from the Firmicutes phylum were positively associated with urinary arsenic concentrations at 6 weeks of age, while 15 genera, including Bacteroides and Bifidobacterium were negatively associated. Notably, effects were stratified by sex and feeding status, with male and formula fed infants more susceptible to arsenic-related effects on the microbiome [128]. This is in contrast with findings in CD-1 mice that female mice were more sensitive to arsenic-induced microbiome perturbation [127].…”
Section: Arsenic Perturbation Of the Microbiomementioning
confidence: 67%
“…However, there is little similarity in compositional shifts during arsenic exposures in different studies. For instance, in Dong et al, Enterobacteriaceae were effectively the only taxa enriched in the high arsenicexposed population of Bangladeshi children [129], while Hoen et al reported a strong negative association between Enterobacteriaceae and urinary arsenic in US infants [128]. Nutritional factors may help explain differences between studies.…”
Section: Arsenic Perturbation Of the Microbiomementioning
confidence: 99%
“…The New England region of the United States has elevated arsenic due principally to natural geologic inputs. Analysis of stool microbiome composition of 204 New Hampshire infants found several genera within the Firmicutes to be suppressed; 15 genera were negatively correlated with urine arsenic levels, including Bacteroides and Bifidobacterium (Hoen et al, 2018). A comparison of stool microbiomes of Bangladesh children exposed to 10 ppb versus >50 ppb arsenic in drinking water (Dong et al, 2017) revealed microbiome compositional shifts, with Proteobacteria and arsB and arsC copy number increasing at the higher arsenic exposure (Dong et al, 2017).…”
Section: Arsenic Perturbation Of the Microbiomementioning
confidence: 99%